Affordable privacy co-living solutions for entry-level office workers in Bonifacio Global City - Padilla, Micaela S.
Housing stress is a major concern for Filipino office workers. The standardized ratio of setting aside '30% of income to rent' cannot be applied to the average Filipino, who can give up at most only 15% of their income to afford other necessities. This limits the housing options of entry-level office workers -- fresh graduates with average salaries who often turn to uncomfortable bed spaces to live closer to work and avoid long commutes. To offset the increasingly unaffordable real estate in Bonifacio Global City, the Philippines' second-largest central business district, co-living apartments have become popular in its vicinity. However, the standard of these co-living spaces is incomparable to that of the global co-living standard, as privacy is the first to be sacrificed in favor of accessibility and attainability. This project aims to bridge the gap between the standard of co-living in the Philippines and that of the global standard by providing better living conditions for tenants through architecture at a portion of the cost via funding from private companies whose workers will benefit from the project. This was achieved through online research on current co-living apartments, as well as interviews of young adults who have lived in Philippines co-living apartments. This project is in Brgy. Pembo, Makati where land is less expensive yet still accessible to Bonifacio Global City via a short commute. Given the size of the lot, the project was expanded vertically to maximize space and differentiate the public and private access areas. The ground floor was dedicated to commercial spaces, the second floor was assigned to the co-living spaces, and the third to seventh floors were reserved for the residents' quarters. The residential floors were divided into quarters to provide sufficient privacy for each tenant without compromising ventilation. To accommodate forty-eight tenants to a floor, rooms were grouped into six to a unit with a communal kitchen, two toilets, and two baths.